2003
DOI: 10.1093/carcin/bgg079
|View full text |Cite
|
Sign up to set email alerts
|

Phenobarbital at low dose exerts hormesis in rat hepatocarcinogenesis by reducing oxidative DNA damage, altering cell proliferation, apoptosis and gene expression

Abstract: Our recent research indicated that phenobarbital (PB) may inhibit the development of N-diethylnitrosamine (DEN)-initiated pre-neoplastic lesions at low doses in a rat liver medium-term bioassay (Ito test), while high doses exhibit promoting activity. This raises the question of whether treatment with low doses of PB might reduce cancer risk. For clarification, male 6-week-old F344 rats were treated with PB at doses of 0, 2, 15 and 500 p.p.m. in the diet for 10 or 33 weeks after initiation of hepatocarcinogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 38 publications
3
46
1
1
Order By: Relevance
“…This reducalthough the detailed mechanism underlying this response is obscure. Kinoshita et al (2003) reported that low-dose treatment with phenobarbital, which is a nongenotoxic carcinogen like DDT (Harada et al, 2003), induced a and enzyme induction.…”
Section: Discussionmentioning
confidence: 99%
“…This reducalthough the detailed mechanism underlying this response is obscure. Kinoshita et al (2003) reported that low-dose treatment with phenobarbital, which is a nongenotoxic carcinogen like DDT (Harada et al, 2003), induced a and enzyme induction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that treatment with PB increased mRNA expression and protein levels of CYP2B in a twostage liver carcinogenesis bioassay in rats (Kinoshita et al, 2003;Waxman and Azaroff, 1992). The nuclear translocation of CAR induced by PB stimulates the expression of various genes that enhance hepatic tumor promotion (Deguchi et al, 2009;Kawamoto et al, 1999).…”
mentioning
confidence: 99%
“…The CYP family generates ROS as byproducts of microsomal oxidation, and PB, a CYP2B1/2 inducer, has been shown to increase hydroxyl radical levels in the livers of rats (Kinoshita et al, 2003;Waxman and Azaroff, 1992). Imaoka et al (2004) reported that CYP2B1 induction by PB induces ROS production and genomic DNA oxidation that may contribute to tumor promotion by PB.…”
Section: Discussionmentioning
confidence: 99%
“…PB induces a large spectrum of drug metabolizing enzymes, including cytochrome P450 family 2 subfamily B (CYP2B) in the liver of rats (Kinoshita et al, 2003;Waxman and Azaroff, 1992). In addition, it has been shown that microsomal reactive oxygen species (ROS) production and production of thiobarbituric acidreactive substances (TBARS) induced with increasing Cyp2b induction due to PB treatment are involved in the liver tumor-promoting effect in rats (Morita et al, 2011).…”
Section: Introductionmentioning
confidence: 99%